The Role of Strategic Intelligence in Managerial Decision-Making in Preparatory Schools in The Center of Erbil Governorate - Nozad Faidh Jameel Qashqai; Abdulrazaq kamal Nuri (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research seeks to uncover the role of strategic intelligence and its dimensions (foresight, future visioning, partnership, motivation, and creativity) in administrative decision-making, in order to try to find out the extent to which there is a clear vision among the principals and their assistants in preparatory schools in the center of Erbil governorate, for strategic intelligence and decision-making Administrative and field framework to identify the nature of the relationship and the effect between the two variables, and to reach the objectives of this research. The research adopted the descriptive and analytical approach in dealing with its variables. A hypothetical scheme for the research was designed expressing its main assumptions and the questionnaire was used as a tool to collect data and it was distributed to (104) managers and assistants (26) preparatory schools as a sample for research. From (50) community preparatory schools for research, (100) questionnaires were retrieved valid for analysis, and a set of statistical methods were used to determine the results, and through the computer program, spss.v-24, the research reached a set of conclusions, the most important of which is the existence of a positive relationship between the dimensions of the variable The independent group, separately and the adopted variable, and the presence of an average significant effect of the dimensions of strategic intelligence influencing administrative decision-making, and I consider that the foresight dimension is the most influential dimension in promoting administrative decision-making in these schools, and the research ended with a set of proposals that serve the research in particular and the sector General educational.